Business-to-business relationship quality - Vieira, Armando Luís (2015)
Relationship quality (RQ) is increasingly seen as a key factor of competitive advantage, replacing service quality and customer satisfaction as a source of superior performance. Despite the crucial role that relationship managers play in building business-to-business (828) relationships, little research has looked at the antecedents of RQ from an interpersonal perspective. In order to respond to the numerous calls for clarification, for there is still some ambiguity around this topic, this study aims to provide a better understanding of the nature and determinants of RQ. A combination of a literature review and the results of a series of interviews with relationship managers of hotels operating in Portugal and their counterparts in corporate clients informed the development of a model, which was subsequently tested using LISREL. Findings highlighted the association between the presence of designated client managers and high quality business relationships, and suggested directions to improve the performance of organisations in building 828 RQ.